The Potential of Local Culture as a Science-Based Educational Media: a Sustainable Solution for Waste Management to Achieve The SDGs - Rafiatul Hasanah; Frista Nova Ayuningtyas; Safira Nurmalinda Rahmadita (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
The global waste crisis necessitates educational innovations to foster ecological awareness and support Sustainable Development Goal (SDG) 12 on responsible consumption and production. This study investigates the potential of the Jember Fashion Carnaval (JFC) as a science-based educational medium for environmental pollution and waste management. Using a qualitative case study design, data were collected via interviews, observation, documentation, and content analysis, with validity ensured through source and methodological triangulation. Findings reveal that the JFC consistently applies 3R principles (Reduce, Reuse, Recycle) by utilizing approximately 40% inorganic waste—such as plastics and cardboard—in costume production. Furthermore, the festival creatively highlights local culture, promoting it through digital media and international collaborations. Ultimately, this practice demonstrates the JFC's tangible contribution to sustainable development, proving it can effectively serve as science-based community education through a practical ‘learning by doing’ approach.